IMPLEMENTASI PENILAIAN BERBASIS KELAS DALAM PEMBELAJARAN IPA BERBASIS INQUIRI DI SMP NEGERI 4 MUARA BUNGO - elda fitri (LP3M STKIP Muhammadiyah Muara Bungo, 2022)
This study aims to improve students' basic competence in science subjects on the subject of motion of objects and living things in the surrounding environment through the implementation of classroom-based assessment in inquiry-based science learning. This type of research is classroom action research, which consists of two cycles. Each cycle consists of four stages, namely action plan, action implementation, observation/ evaluation, and reflection. This research was conducted in class VIII.5 of SMP Negeri 4 Muara Bungo involving 30 students for the 2021/2022 academic year. Data about students' cognitive competence was collected by the test method, data about students' affective competence was collected by observation method, data about students' psychomotor competence was collected by observation method. Furthermore, the data were analyzed descriptively. The findings of this study indicate that (1) there is an increase in students' cognitive competence from an average value of 69.80 with classical learning completeness of 53.85% in the first cycle to an average value of 77.40 with classical learning completeness of 87.18% in the first cycle. II, (2) there was an increase in the affective competence of students from an average value of 80.30 with a good category in the first cycle to an average value of 84.90 with a very good category in the second cycle, and (3) an increase in the psychomotor competence of students from an average value of 66.40 with a sufficient category in the first cycle to an average value of 77.18 with a good category in the second cycle.